War room [videorecording (DVD)] - Kendrick, Alex, 1970-; Shirer, Priscilla, 1974-; Stallings, T. C.; Abercrombie, Karen, 1956- (Sony Pictures Home Entertainment, 2015)
Tony and Elizabeth Jordan have it all; great jobs, a beautiful daughter, and their dream house. But appearances can be deceiving. Their world is actually crumbling under the strain of a failing marriage. While Tony basks in his professional success and flirts with temptation, Elizabeth resigns herself to increasing bitterness. But when Elizabeth meets her newest client, Miss Clara, and is challenged to establish a "war room" and a battle plan of prayer for her family.